Analysis Of Differences in Pregnant Women's Knowledge and Readiness Regarding Childbirth Preparation Before and After Counseling (At TPMB Desak Putu Lita. A) Surabaya - Komariyah, Siti; Siti Muntowiyah (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
Knowledge and preparedness for childbirth are two of the benchmarks for the success of the delivery process. As pregnancy progresses, the mother should be educated about childbirth and the necessary preparations. Counseling makes it easier for pregnant women and health workers to discuss health issues, namely, preparation and readiness for childbirth. Objective, analyzing differences in knowledge and readiness of pregnant women to face childbirth before and after being given counseling about childbirth preparation at Independent Practice Places for Midwives Desak Putu Lita Anggraeni in Surabaya. This research employed a pre-experimental design with a cross-sectional, one-group, pretest-posttest approach. The sample was taken using a total sampling technique of 30 participants. The dependent variable was the level of knowledge and readiness, which was measured using a questionnaire. Data were analyzed using the Wilcoxon Signed-Rank Test to differentiate between the two variables. Results of analysis of pregnant women's knowledge using the Wilcoxon Signed-rank test. The calculated z value = -3.357 with a significance of 0.001 is smaller than 0.05. The highest increase in knowledge about psychology is the need to feel loved by one's husband, specifically from 10 (33%) to 30 (100%). The results of the analysis of pregnant women's readiness to face childbirth yielded a calculated z-value of -3.00, with a significance level of 0.003, which is less than 0.05. The highest increase in participants' readiness regarding contraceptive methods after delivery is from 17 (57%) to 29 (97%). There are differences in the knowledge and readiness of pregnant women to face childbirth. Counseling increases the knowledge and readiness of pregnant women to face childbirth. Suggestions for Independent Practice Places for Midwives to improve educational methods regarding childbirth preparation that are effective and easily accessible.